THE THERMODYNAMICS OF THE AQUEOUS CARBON DIOXIDE FLUID WITHIN THIN PORES - Belonoshko A.B. (My University, 1989)
The density functional method was used to study the properties of a binary mixture watercarbon dioxide confined within an infinitely long cylindrical pore of 8 to 25 Å in diameter, over a wide range of temperatures, pressures and compositions. Interaction with pore walls was calculated through the use of van der Waals and Kazimir-Polder attractive forces; the intermolecular interaction was calculated by means of the spheric-symmetrical approximation. The calculations show that the pore fluid differs markedly in composition from the bulk fluid with which it is in equilibrium at the same temperatures and pressures. The difference diminishes regularly with increasing pore size to become negligible at a pore diameter of 25 Å. The results of the work presented here provide a physical explanation of the Johannes-Schreyer (1981) experiments. Reasons are offered for the predominantly carbon dioxide composition of fluid inclusions formed from the fluid of aqueous bulk composition. The relationship between the size of fluid-filled pores and the geometry of the MgO-SiO2-H2O-CO2 diagram in the T-XCO2 coordinates is discussed. The low activity of water during metamorphism has been explained.